US FDA Warning Letters of CAPA Violations: A Review - Deshpande, Pavan; Agawane, Rutuja; Tatikola, Sarath C.; Vasantharaju, Surenahalli G. (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2020)
United States Food and Drug Administration (USFDA) is a federal agency functioning under United States Federal Executive Departments, which strives to regulate the food products and drug substances being manufactured or brought into US market, upholding Quality and Safety as prime goals. It takes care of its goals by inspecting firms which market products in the United States. It chalks out good manufacturing procedures for obtaining quality end-products. Based on inspections conducted and data collected thereby, those not abiding by rules shall be issued with Warning Letters and marketing license shall be cancelled for those who fail to justify the warning letter. This brings about discipline amongst manufacturers and sets a goal of quality that needs to be achieved to survive in market.
Keywords: regulated markets